2016
DOI: 10.1111/andr.12156
|View full text |Cite
|
Sign up to set email alerts
|

Anogenital distance as a marker of androgen exposure in humans

Abstract: SUMMARYAbnormal foetal testis development has been proposed to underlie common disorders of the male reproductive system such as cryptorchidism, hypospadias, reduced semen quality and testicular germ cell tumour, which are regarded as components of a 'testicular dysgenesis syndrome'. The increasing trends and geographical variation in their incidence have been suggested to result from in utero exposure to environmental chemicals acting as endocrine disruptors. In rodents, the anogenital distance (AGD), measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
116
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(124 citation statements)
references
References 98 publications
1
116
6
1
Order By: Relevance
“…Recently, an in silico approach revealed that the DEHP molecule may compete with DHT and/or testosterone for SHBG [6]. AGD is a biomarker of androgen exposure during the fetal testis development period in rodents as well as in humans [21], whereas sperm concentration and motility are the most significant predictor of human fertility [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, an in silico approach revealed that the DEHP molecule may compete with DHT and/or testosterone for SHBG [6]. AGD is a biomarker of androgen exposure during the fetal testis development period in rodents as well as in humans [21], whereas sperm concentration and motility are the most significant predictor of human fertility [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Hence, AGD could be measured at any postnatal age in rats and used to retrospectively decipher the level of fetal androgen exposure during the MPW (11,21). In human males, AGD shows similar male-female differences as in rats (11,(24)(25)(26), and lower AGD has been related to the occurrence of TDS disorders evident at birth (27)(28)(29)(30)(31)(32)(33) and, in a majority of studies, to lower sperm counts (34)(35)(36)(37) and hormone levels (38,39) in adult men, similar to rats (reviewed in ref. 11).…”
Section: Introductionmentioning
confidence: 99%
“…As there is already a substantial body of similar association data in human males (Table 1), it is reasonable to propose that an MPW exists in humans, so that studies to identify potential causes of TDS disorders should focus on the presumptive MPW (~8-14 weeks' gestation). While such studies have several inherent limitations, the measurement of AGD in newborn offspring, as an indicator of androgen exposure within the presumptive MPW, will play an important role, even if interindividual variation may restrict its usefulness to population-based studies (11,25,36).…”
mentioning
confidence: 99%
“…In humans, prenatal exposure to phthalates has been associated with altered sex steroid levels [3436] and de-masculinized phenotypes among boys, including reduced anogenital distance [37]. In turn, anogenital distance is considered a sensitive marker of androgen activity in early gestation [38] and correlates with sex-specific neurobehaviors [39]. Dibutyl phthalate (DBP) is a plasticizer that has been used extensively in toys and personal care products [40].…”
Section: Mechanism 2: Altered Sex Steroid Levelsmentioning
confidence: 99%